Frequency of use controls chemical leaching from drinking-water containers subject to disinfection - Andra, Syam S.; Shine, James P.; Makris, Konstantinos C. (My University, 2011)
Microbial-, and chemical-based burden of disease associated with lack of access to safe water continues to primarily impact developing countries. Cost-effective health risk-mitigating measures, such as of solar disinfection applied to microbial-contaminated water stored in plastic bottles have been increasingly tested in developing countries adversely impacted by epidemic water-borne diseases. Public health concerns associated with chemical leaching from water packaging materials led us to investigate the magnitude and variability of antimony (Sb) and bromine (Br) leaching from reused plastic containers (polyethylene terephthalate, PET; and polycarbonate, PC) subject to UV and/or temperature-driven disinfection. The overall objective of this study was to determine the main and interactive effects of temperature, UV exposure duration, and frequency of bottle reuse on the extent of leaching of Sb and Br from plastic bottles into water. Regardless of UV exposure duration, frequency of reuse (up to 27 times) was the major factor that linearly increased Sb leaching from PET bottles at all temperatures tested (13–47 °C). Leached Sb concentrations (∼360 ng L−1) from the highly reused (27 times) PET bottles (minimal Sb leaching from PC bottles, <15 ng L−1) did not pose a serious risk to human health according to current daily Sb acceptable intake estimates. Leached Br concentrations from both PET and PC containers (up to ∼15 μg L−1) did not pose a consumer health risk either, however, no acceptable daily dose estimates exist for oral ingestion of organo-brominated, or other plasticizers/additives compounds if they were to be found in bottled water at much lower concentrations. Additional research on potential leaching of organic chemicals from water packaging materials is deemed necessary under relevant environmental conditions.
Keywords: Antimony; Bottled water; Bottle reuse; Bromine; Polyethylene terephthalate; Polycarbonate; Polybrominated biphenyl ethers